Pharmacological Treatment of Peptic Ulcer: Eradication of Helicobacter Pylori Infection - Roong-apinan, Sukij (Journal of Basic and Applied Pharmacology, 2015)
Because of the widespread arousing interest in Helicobacter pylori infection,pharmacological treatment for peptic ulcer faces great changes. Although severalcontroversial aspects about this infection are still suspended in medical profession. There area lot of evidences which have proven the benefits of eradication H pylori from the gut of peptic patients. Moreover, NIH consensus conference has approved eradication H pylori inevery peptic patient who is infected with this spiral organism. This article is hoped to beuseful for catching up pharmacological management on this catchy name, H pyloriin pepticdisease. It reviews about importance, basic clinical studies, and gastric pharmacology. Various regimens of treatment are summarized. Some of general considerations in drugtherapy are also discussed.